Action Identification of The Employees - AL-Khazraji, Maysam Younus Jabbar; AL-Mufti, Diar Awni Fadhil (Al-Adab Journal, 2021)
The theory of action identification is based on far reaching objectives and the ways of their achievement. To achieve the research objectives, the researcher adopted the theory of action identification by Vallacher & Wegner (2011) for designing the instrument for measuring action identification consisting of 30 items. The research sample consisted of 400 employees aged between (23-62), with different education levels (secondary, diploma, bachelor) (graduate) in Baghdad governorate. The results revealed that: The sample of employees highly enjoyed action identification. The correlational differences in action identification among the employees are as follows; There is a significant difference in action identification with reference to gender variable. There is no significant difference inaction identification with reference to education level variable. There is no significant difference inaction identification with reference to age variable. The study came up with a number of recommendations as follows; - Activating the role of psychological guides and mentors through conferences and symposiums. - Educating the employees with the knowledge of action identification. Finally, a number of further studies are suggested..